Peningkatan Ekonomi Rumah Tangga Petani Melalui Sistem Elektronik Rencana Definitif Kebutuhan Kelompok Tani dan Pemanfaatan Lahan Pekarangan Pangan Lestari - Alam, Megawati Citra; Aji, Satriya Bayu; Rosadi, Imam; Artini, Widi; Kustiani, Edy; Supandji, Supandji (Kadiri University, 2024)
This community service activity explores ways to improve the economy of farmer households through an electronic system for definitive plans for the needs of farmer groups and the role of women farmer groups through sustainable use of food plots. By coordinating this program, the synergy between agricultural activities is created to achieve broader goals regarding food security and sustainable natural resource management. Challenges such as limited access to subsidized fertilizers encourage the use of E-RDKK, which requires farmer collaboration for effective planning and distribution. Optimizing P2L is an alternative for sustainable food production in the home garden. Reduce dependence on external resources such as subsidized fertilizer and strengthen local food security. This activity was carried out using an open questionnaire before (pre-test) and after (post-test) lecture sessions, discussion sessions, and training sessions. Next, the team continued with a focus group discussion (FGD) session for the follow-up stage of the training. Then, proceed with evaluation using a qualitative approach to thematic analysis techniques and cross-tabulation. The team looked for themes that emerged from the questionnaire response data and recorded the FGD transcripts. Apart from that, data organization was also carried out with the help of the MAXQDA 2020 Application. This activity provides insight into how the RDKK and P2L programs can be an essential tool in improving the economy of farmer households through sustainable food security at the local level, primarily through community-based land management strategies. The policy recommendations and sustainable practices resulting from this activity will support similar efforts in other regions in Indonesia that face the same challenges.Kegiatan pengabdian kepada masyarakat ini mengeksplorasi cara peningkatan ekonomi rumah tangga petani melalui sistem elektronik rencana definitif kebutuhan kelompok tani dan peran kelompok wanita tani melalui pemanfaatan lahan pekarangan pangan lestari secara berkelanjutan. Dengan mengkoordinasikan program ini, tercipta sinergi antar aktivitas pertanian untuk mencapai tujuan yang lebih luas mengenai ketahanan pangan dan pengelolaan sumberdaya alam yang berkelanjutan. Tantangan seperti akses terbatas pada pupuk bersubsidi mendorong penggunaan E-RDKK, yang memerlukan kolaborasi petani untuk perencanaan dan distribusi yang efektif. Pengoptimalisasian P2L menjadi alternatif produksi pangan yang berkelanjutan di pekarangan rumah. Mengurangi ketergantungan terhadap sumberdaya eksternal seperti pupuk bersubsidi dan memperkuat ketahanan pangan lokal. Kegiatan ini dilakukan menggunakan kuesioner terbuka dilakukan sebelum (pra-tes) dan sesudah (pasca-tes) sesi ceramah, sesi diskusi, dan sesi pelatihan. Selanjutnya, tim melanjutkan dengan sesi focus Group Discussions (FGD) untuk tahap tindak lanjut dari pelatihan. Kemudian dilanjutkan dengan evaluasi menggunakan pendekatan kualitatif untuk teknik analisis tematik dan tabulasi silang. Tim, mencari tema yang muncul dari data respons kuesioner dan mencatat transkrip FGD. Selain itu, organisasi data juga dilakukan dengan bantuan Aplikasi MAXQDA 2020. Kegiatan ini memberikan wawasan tentang bagaimana RDKK dan program P2L dapat menjadi alat penting dalam peningkatan ekonomi rumah tangga petani melalui ketahanan pangan yang berkelanjutan di tingkat lokal. Terutama melalui strategi manajemen lahan berbasis komunitas. Rekomendasi kebijakan dan praktik berkelanjutan yang dihasilkan dari kegiatan ini diharapkan akan mendukung upaya-upaya serupa di wilayah lain di indonesia yang menghadapi tantangan yang sama.